Peran Matematika Dasar Dalam Optimalisasi Teknik Pertanian Modern - Mendrofa, Serlin Jessica; Jellianus (CV. SINAR HOWUHOWU, 2025)
Basic mathematics plays a crucial role in improving the effectiveness and efficiency of modern agricultural techniques. The application of mathematical concepts such as algebra, geometry, statistics, and calculus allows for more accurate decision making in various aspects of agriculture. Optimizing resource use, analyzing crop yield data, managing irrigation systems, and land mapping are some examples of applications of mathematics that have been proven to be able to increase agricultural efficiency by up to 30% in certain scenarios. This article discusses how the integration of mathematics in agricultural practices can increase productivity and contribute to more sustainable agriculture.